Classroom, Home and Peer Environment Influences on Student Outcomes in Science and Mathematics: An Analysis of Systemic Reform Data - Fraser, Barry; Butler Khale, J. (Routledge, 2007)
Using secondary analysis of a large database from a Statewide Systemic Initiative, we examined the effects of several types of environments on student outcomes. Over 3 years, nearly 7,000 students in 392 classes in 200 different schools responded to a questionnaire that assesses class, home, and peer environments as well as student attitudes. Students also completed an achievement measure that, developed by scientists, teachers, and science educators, was not aligned with any particular curriculum. Students were enrolled in middle‐school science and mathematics classes in schools that had participated in the Statewide Systemic Initiative. Rasch analyses allowed us to compare across student cohorts and across schools. Findings confirmed the importance of extending research on classroom learning environments to include the learning environments of the home and the peer group. Although all three environments accounted for statistically significant amounts of unique variance in student attitudes, only the class environment (defined in terms of the frequency of use of standards‐based teaching practices) accounted for statistically significant amounts of unique variance in student achievement scores. The findings are supported by other studies of systemic reform in the United States.